Subnormal sensitivity of neutrophils to complement split product C5a in rheumatoid arthritis: relation to complement catabolism and disease extent. Issue 8 (August 1985) - Elmgreen, J; Hansen, T M
Abstract : The capacity of circulating neutrophils for activation by complement was studied in outpatients with classical or definite rheumatoid arthritis during treatment with dextropropoxyphene only. Analysis of dose-response in the Boyden chamber assay of chemotaxis showed that sensitivity to the potent, complement derived anaphylatoxin, C5a, was markedly decreased, especially in those patients with few joints involved. In contrast, peak response to C5a was within the normal range. Increased complement 3c split products in plasma of the patients suggested involvement of complement cascade reactions. Subnormal sensitivity of neutrophils to phlogistic mediators released by complement may tend to limit their recruitment and potentially tissue destroying secretion locally in rheumatoid arthritis.